COMMONALTIES BETWEEN PASHTUN VALUES AND ISLAMIC VALUES: A RESEARCH STUDY IN THE CONTEXT OF ISLAMIC HISTORY (Al-Aasar, 2025)
This article investigates the commonalities between Pashtun values and Islamic values. The Pashtunwali code is unwritten set of principles guiding the Pashtun society that play a vital and significant role social gatherings. These values fostering unity, resolving conflicts, fairness and Justice. These values are deeply embedded in Pashtun culture and reflection of their identity and sense of honor and dignity. Among the most prominent is the Jirga system (tribal council) the cornerstone of Pashtunwali that provide a peaceful and fair platform for resolving disputes through mutual consultation. Similarly events like weddings, funerals, and festival gatherings not only strengthen family and tribal bonds but also shared cultural norms. Despite this, the alignment of many Pashtunwali traditions with Islamic teachings such as hospitality, peacebuilding, and collective consultation highlights their spiritual and moral relevance. This paper examines the commonalities between Pashtun values and Islamic values according to Islamic perspective.